2016
DOI: 10.1007/s12665-016-5500-1
|View full text |Cite
|
Sign up to set email alerts
|

Simulating seismic chimney structures as potential vertical migration pathways for CO2 in the Snøhvit area, SW Barents Sea: model challenges and outcomes

Abstract: Carbon Capture and Storage (CCS) activities at the Snøhvit field, Barents Sea, will involve carrying out an analysis to determine which parameters affect the migration process of CO2 from the gas reservoir, to what degree they do so and how sensitive these parameters are to any changes. This analysis will aim to evaluate the effects of applying a broad but realistic range of reservoir, fault and gas chimney properties on potential CO2 leakage at various depths throughout the subsurface. Fluid flow might take p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The leakage along the fault planes has been previously reported as main link between deep thermogenic reservoirs and the shallow subsurface [13,17,32,33]. In this study, we have shown that the intrinsic fault properties (capillary entry pressure and permeability) play a major role in hydrocarbon leakage from reservoirs during deglaciations.…”
Section: Leakage and Accumulation In Shallow Trapsmentioning
confidence: 52%
See 2 more Smart Citations
“…The leakage along the fault planes has been previously reported as main link between deep thermogenic reservoirs and the shallow subsurface [13,17,32,33]. In this study, we have shown that the intrinsic fault properties (capillary entry pressure and permeability) play a major role in hydrocarbon leakage from reservoirs during deglaciations.…”
Section: Leakage and Accumulation In Shallow Trapsmentioning
confidence: 52%
“…With this approach, we aim to reveal the impact of Pliocene-Pleistocene glaciations on hydrocarbon remigration and leakage from the Snøhvit and Albatross fields, which could serve as the analogue for de-risking of petroleum prospects in the Barents Sea. The results will also have implications for CO 2 capture and storage efforts and associated risks at Snøhvit field [8,32]. …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Walter et al [33] provides estimates of the risk of brine discharge into freshwater aquifers due to CO2 injection into geological formations. Key parameters influencing the CO2 migration process from the gas reservoir in the Snøvit area, Barents Sea were determined by means of numerical modelling with DuMu x [34]. The authors identify potential migration pathways and their extent, i.e., faults, gas chimneys in an off-shore mostly sandy reservoir located in the Tubåen Formation (at 2560-2670 m below sea surface).…”
Section: Modelling Costorage In Geological Formations Using Dumu Xmentioning
confidence: 99%
“…The numerical modeling of the gas leakage and chimney forming mechanisms is very challenging. Tasianas et al [20] modeled the gas leakage along pre-existing conducting geological structures on the reservoir scale. They considered the flow along three types of structures preliminary set up in the model: faults, fracture network penetrating the reservoir's caprock, and high permeable fluid conduits.…”
Section: Introductionmentioning
confidence: 99%